Child Poverty and Food Scheme in Rural South African Schools: The Prospects and Limits Towards Improving the Emotional Well-Being of The Elementary School Students - Ifeanyichukwu Okoye, Felix; Amartey Mensah, Prince (International Journal of Scientific Research and Management (IJSRM), 2021)
The research examines the impact of poverty on the emotional well-being of elementary school students in South African rural communities. In order to understand this phenomenon, the study investigates the question on: how does poverty affect the emotional well-being of elementary school students in South Africa? The non-empirical study explores the literature from related studies to answer the research question. The literature review critically examines the effect of poverty on the emotional well-being of children, as well as the strategies used by the government to alleviate the poverty impact at rural school children. The strategies were found to have implementation deficiencies which enables the researcher to argue on the importance of improving the implementation strategies. The   finding also reveals that despite the government’s interventions to curb the problem of child poverty, yet there are policy implementation “gaps” here and there. The study recommends more study and consistent evaluation of the respective policy framework. It also recommends that the socio-economic status of people leaving in the rural area should be improved and the affected students should be engaged, and proper development response should be executed to guarantee a sustainable food security. Finally, more study and consistent evaluation of the feeding-scheme programme or policy is a sinequanon. The recommendation for Covid-19 is added for publication purposes.